Educational parenting practices in mother-child social interaction (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The study of mother-child interactions favors the elaboration of effective interventions. The objective of this paper is to describe, compare and correlate social interactions established between mothers and their children with respect to the maternal behavior and the child repertoire, controlling the presence or absence of behavior problems and the child gender as well. Participants were 68 married mothers and their pre-school and school children, with and without behavior problems, equally distributed to a case-control design, concerning gender and schooling of those children. Comparative and correlational analyses were performed in relation to educational practices and child behaviors. Results indicate differentiated social interactions regarding the communication, affection and limits, and there are in the non-clinic group more positive practices which are contingent on the expected behaviors of children. On the other hand, non-clinic children are more skilled and contingent on the maternal behaviors. Few differences were found in the practices with boys and girls, but there is widespread use of negative educational practices among the boys.
Keywords: educational practices; behaviour problems; social skills; gender; schooling; maternal socio-demographic variables